2022
DOI: 10.3390/mi13030432
|View full text |Cite
|
Sign up to set email alerts
|

N-Type Nanosheet FETs without Ground Plane Region for Process Simplification

Abstract: This paper proposes a simplified fabrication processing for nanosheet Field-Effect Transistors (FETs) part of beyond-3-nm node technology. Formation of the ground plane (GP) region can be replaced by an epitaxial grown doped ultra-thin (DUT) layer on the starting wafer prior to Six/SiGe1-x stack formation. The proposed process flow can be performed in-situ, and does not require changing chambers or a high temperature annealing process. In short, conventional processes such as ion implantation and subsequent th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 21 publications
1
4
0
Order By: Relevance
“…Hence, a V SPC narrower than 15 nm would be preferred for a better annealing effect of NS FETs. This tendency coincides with the development trend of current NS FETs toward a narrower V SPC for better packing density [26].…”
Section: Resultssupporting
confidence: 85%
“…Hence, a V SPC narrower than 15 nm would be preferred for a better annealing effect of NS FETs. This tendency coincides with the development trend of current NS FETs toward a narrower V SPC for better packing density [26].…”
Section: Resultssupporting
confidence: 85%
“…Although device scaling approaches have reached an extreme level, suppressing short-channel effects by using fin FETs is still difficult. As a solution for 3D structure devices, FETs composed of multiple nanosheets with a gate-all-around (GAA) structure are good candidates for replacing fin FETs at the 5 nm technology node and beyond [ 5 , 6 ]. One of the most important achievements in 3D device manufacturing is the production of high and stable doping in the source and drain (S/D) region [ 1 , 3 ].…”
Section: Introductionmentioning
confidence: 99%
“…P-doped Si S/D that uses the in situ-doped epitaxy process has been developed because this process flow accepts a more accurate dopant concentration without additional thermal treatment [ 8 , 9 ]. However, in situ doping layers grown on the Si surface exhibit inherent defects that correlate with the growth condition and dopant density [ 5 ] due to a solubility limitation [ 10 , 11 ]. Investigations on P-doped Si films have suggested that donor–vacancy complexes can cause some of the doped P atoms to not emit free carriers; this phenomenon is called electrical deactivation [ 12 , 13 , 14 ].…”
Section: Introductionmentioning
confidence: 99%
“…Interestingly, some novel processes relating thin film electronic devices were reported in this Special Issue [14,15]. K. S. Lee employed a process simplification for n-type nanosheet FETs without a ground plane region [14]; the proposed flow could be performed in situ, without the requirement of changing chambers or a high-temperature annealing process.…”
mentioning
confidence: 99%
“…Interestingly, some novel processes relating thin film electronic devices were reported in this Special Issue [14,15]. K. S. Lee employed a process simplification for n-type nanosheet FETs without a ground plane region [14]; the proposed flow could be performed in situ, without the requirement of changing chambers or a high-temperature annealing process. In addition, X. Ding et al successfully realized the efficient multi-material structured thin film transfer to elastomers for stretchable electronic devices by combining bench-top thin film structuring with solvent-assisted lift-off methods [15].…”
mentioning
confidence: 99%